Modeling, Optimization And Sensitivity Analysis Of The Final Pit Limits For A Lignite Deposit - J. Mastoris; E. Topuz (Society for Mining, Metallurgy & Exploration, 1996)
The problem of defining the optimum final limits of an open-pit mine has challenged the mining industry for the last three decades. The difficulty results mainly from the great number of variables involved and from the sheer computational effort required in real-life applications. An actual lignite deposit is used in this study to introduce and apply a new methodology that can be used as a basis for surface-mine design optimization. A geologic-reserves model of the deposit is first developed with the use of an integrated geostatistical-modeling package. The model is transformed into an economic one through the use of flexible objective function formulation(s). The final open-pit limits are then optimized using a competent commercial optimizer, and comparative-sensitivity analyses are performed to study the effect of some basic mining and economic parameters on the optimal pit design. The conclusions drawn can develop useful guidelines for decision making by the mine operator.